Smaller introducer sheaths for REBOA may be associated with fewer complications. Issue 6 (December 2016) - Teeter, William A.; Matsumoto, Junichi; Idoguchi, Koji; Kon, Yuri; Orita, Tomohiko; Funabiki, Tomohiro; Brenner, Megan L.; Matsumura, Yosuke
Abstract : Introduction: Large arterial sheaths currently used for resuscitative endovascular balloon occlusion of the aorta (REBOA) may be associated with severe complications. Smaller diameter catheters compatible with 7Fr sheaths may improve the safety profile. Methods: A retrospective review of patients receiving REBOA through a 7Fr sheath for refractory traumatic hemorrhagic shock was performed from January 2014 to June 2015 at five tertiary-care hospitals in Japan. Demographics were collected including method of arterial access; outcomes included mortality and REBOA-related access complications. Results: Thirty-three patients underwent REBOA at Zone 1 (level of the diaphragm). Most patients were male (70%), with a mean age (+SD) 50 ± 18 years, mean BMI 23 ± 4, and a median [IQR] ISS of 38 [34, 52]. Ninety-four percent of patients presented after sustaining injuries from blunt mechanisms. Twenty-four percent underwent CPR before arrival, and an additional 15% received CPR after admission. Percutaneous arterial access without ultrasound or fluoroscopy was achieved in all patients. Systolic blood pressure increased significantly following balloon occlusion (mean 62 ± 36 to 106 ± 40 mm Hg, p < 0.001). Median total duration of complete initial occlusion was 26 [range 10–35] minutes. Sixteen patients (49%) survived beyond 24 hours, and 14 patients (42%) survived beyond 30 days. Twenty-four-hour and 30-day survival were 48% and 42%, respectively. Of the patients surviving 24 hours (n = 16), median duration of sheath placement was 28 [range 18–45] hours with all removed using manual pressure to achieve hemostasis. Of 33 REBOAs, 20 were performed by Emergency Medicine practitioners, 10 by Emergency Medicine practitioners with endovascular training, and 3 by Interventional Radiologists. No complication related to sheath insertion or removal was identified during the follow-up period, including dissection, pseudoaneurysm, retroperitoneal hematoma, leg ischemia, or distal embolism. Conclusions: 7Fr REBOA catheters can significantly elevate systolic blood pressure with no access-related complications. Our results suggest that a 7Fr introducer device for REBOA may be a safe and effective alternative to large-bore sheaths, and may remain in place during the post-procedure resuscitative phase without sequelae. LEVEL OF EVIDENCE: Therapeutic/care management, level V.